Implementasi Webiot Sistem Absensi Face Dalam Antisipasi Bencana Alam - Ahmad Hunaepi; Ahmad Roihan; Mochamad Yusuf Romdoni (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
Natural disasters are unexpected natural events, have a major impact on every level of society, especially coastal areas such as power generation companies that use coal as a natural resource. Every company hopes to be able to anticipate early and quickly so that employees are maintained and safe. The face attendance system is a monitoring tool combined with a smart gate with a face recognition concept that can be monitored online. Faces that have been registered can be recognized so that the device will act as a trigger to open the door, and vice versa if the face is not recognized, the device will still record and act as a trigger for the door to remain closed. The implementation of the facial attendance system can be used as a data source to calculate the number of employees who are still in and out of the company when a natural disaster occurs.